ChatGPT: a bibliometric analysis and visualization of emerging educational trends, challenges, and applications - Samala, Agariadne Dwinggo; Sokolova, Elizaveta Vitalievna; Grassini, Simone; Rawas, Soha (Institute of Advanced Engineering and Science, 2024)
This study conducts a comprehensive bibliometric analysis and visual exploration of the chat generative pre-trained transformer (ChatGPT) literature in 2023, focusing on its trends, challenges, and applications in education. Using RStudio for bibliometric analysis and VOS viewer for data visualization, this study examines publications from the Scopus database. Following the preferred reporting items for systematic reviews and metaanalyses (PRISMA) guidelines, the systematic review process reinforces the robustness of the analysis. The finding reveals notable trends in the utilization of ChatGPT. Key insights underscore ChatGPT’s increasing role in enhancing engagement, facilitating personalized learning, and fostering student creativity and critical thinking. However, its integration into education encounters obstacles, including ethical considerations, issues of academic honesty, and the imperative for precise usage guidelines; notable applications of ChatGPT encompass language learning, tutoring, automated feedback provision, and functioning as a virtual assistant. These applications showcase ChatGPT’s potential to reshape the educational landscape by introducing innovative pedagogical methods and enriching the student experience. This combined bibliometric and visual analysis provides a comprehensive view of the current status of ChatGPT within the educational domain. It provides a snapshot of the role of ChatGPT in education, offering valuable insights for future research endeavors.